2010
DOI: 10.1007/s00213-009-1750-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated MDMA administration on the motivation for palatable food and extinction of operant responding in mice

Abstract: This study demonstrates that repeated treatment with MDMA decreases the incentive motivation for a palatable food reward and that long-lasting MDMA-induced dopaminergic neurotoxicity increases the resistance to extinction of responding in the absence of reward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Effects after repeated administrations have been investigated in several animal models where the dose and frequency of the applied administration protocols had profound effects on the severity of acute (hyperthermia) and long-term (neurotoxicity, cognition and behavior) responses (O'Shea et al, 1998;Green et al, 2004a, Green et al, 2009, Plaza-Zabala et al, 2010, Viñals et al, 2013. In humans, several single dose placebocontrolled studies have been reported (de la Torre et al, 2000a;Pardo-Lozano et al, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…Effects after repeated administrations have been investigated in several animal models where the dose and frequency of the applied administration protocols had profound effects on the severity of acute (hyperthermia) and long-term (neurotoxicity, cognition and behavior) responses (O'Shea et al, 1998;Green et al, 2004a, Green et al, 2009, Plaza-Zabala et al, 2010, Viñals et al, 2013. In humans, several single dose placebocontrolled studies have been reported (de la Torre et al, 2000a;Pardo-Lozano et al, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…In agreement, neurotoxic doses of MDMA have been shown to produce temporary decreases in striatal DAT binding in mice studies using receptor autoradiography (Trigo et al . 2008; Plaza‐Zabala et al . 2010) or immunohistochemitry (Granado et al .…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the effects of MDMA‐induced dopaminergic neurotoxicity in these behavioural responses, we have selected one non‐neurotoxic and one neurotoxic dose of MDMA. These doses, as well as the time course of administration, were chosen from previous work in our laboratory showing that 3 mg/kg twice a day for 4 days did not produce any change in DAT binding in the striatum of mice, while 30 mg/kg twice a day for 4 days induced a persistent decrease in this binding (Plaza‐Zabala et al . 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple advantages to using pharmacological agents to assess changes in learning and reward-seeking behaviour. For example, pharmacological treatments can be employed during the acquisition of an operant response (Ranaldi et al, 2011) or prior to the extinction session (Aparicio, 2010;Holahan et al, 2010;Plaza-Zabala et al, 2010;Vurbic et al, 2011) to investigate how altering brain chemistry influences the different phases o f reward-based operant tasks. In appetitive extinction, pharmacological manipulation also allows researchers to assess how altering neurotransmitter release peripherally or centrally affects learning and extinction behaviour, and which systems in the brain are implicated in extinction enhancement or resistance (Holahan et al, 2010;Ranaldi et al, 2011).…”
Section: Pharmacological Agonists O F the Dopamine Systemmentioning
confidence: 99%